2019
DOI: 10.1016/j.neuroimage.2018.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Altered temporal variance and functional connectivity of BOLD signal is associated with state anxiety during acute systemic inflammation

Abstract: Altered temporal variance and functional connectivity of BOLD signal is associated with state anxiety during acute systemic inflammation Short title: Neural variance and state anxiety during acute inflammation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 79 publications
3
12
0
Order By: Relevance
“…In addition, growing evidence suggests that the insular cortex, a key node of the SAN, and its functional link to other brain regions play a crucial role in the central representation of inflammation [35][36][37] as well as anxiety or depression 36,38 . Specifically, our findings of reduced functional connectivity regarding the SAN that are also associated with greater PTS symptom severity may be consistent with previous studies that have noted decreased SAN connectivity following induced transient systemic inflammation 39 , as well as the interaction effect between functional connectivity of the brain with clinical symptom severity 18 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, growing evidence suggests that the insular cortex, a key node of the SAN, and its functional link to other brain regions play a crucial role in the central representation of inflammation [35][36][37] as well as anxiety or depression 36,38 . Specifically, our findings of reduced functional connectivity regarding the SAN that are also associated with greater PTS symptom severity may be consistent with previous studies that have noted decreased SAN connectivity following induced transient systemic inflammation 39 , as well as the interaction effect between functional connectivity of the brain with clinical symptom severity 18 .…”
Section: Discussionsupporting
confidence: 92%
“…The NAcc also plays a role in fear conditioning and FE (Fullana et al, 2018). The increasing variance appeared consistent with prior literature showing a positive association between increasing variance and functional efficiency during active cognitive tasks (Garrett et al, 2012(Garrett et al, , 2018Labrenz et al, 2019). The thalamic nuclei were associated with visual (BN-239-PPtha-L) and action execution (BN-233-PMtha-L) functions (Fan et al, 2016 3 ), and their changes in variability seemed related to the experimental environment.…”
Section: Changes In the Variance Of The Bold Signal After Fear Learnisupporting
confidence: 85%
“…Therefore, we expected a decrease of the scaling exponent during fear extinction in the fear-processing brain network, similar to the findings on its suppression with cognitive load (Barnes et al, 2009;Churchill et al, 2016). Simultaneously, we hypothesized that the variance should increase during the task as an indirect index of neural efficiency (Labrenz et al, 2019). We also expected to find residual changes of both LRTC and variance in areas of fear-processing brain network in the post-task resting state, as it was early reported for functional connectivity of the BOLD signal (Schultz et al, 2012;Feng et al, 2015;Martynova et al, 2020).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, it has been demonstrated that the variance of the task-evoked BOLD response was differentially related to aging as well as cognitive performance (Armbruster-Genc et al, 2016;Garrett et al, 2013a). Similarly, spontaneous signal variability in resting state fMRI (rsfMRI) has been associated with age (Grady and Garrett, 2018;Nomi et al, 2017), emotional state (state anxiety; Labrenz et al, 2018), and mental or neural disorders such as stroke (Kielar et al, 2016), Attention Deficit Hyperactivity Disorder (Nomi et al, 2018) or 22q11.2 deletion syndrome (Zöller et al, 2017). From these studies, it was concluded that reductions in BOLD signal variability might serve as an index for deficits in neural processing and cognitive flexibility (Grady and Garrett, 2014).…”
Section: Introductionmentioning
confidence: 99%